IMPLEMENTATION THE PROBLEM BASED LEARNING MODEL USING THE GASING METHOD TO INCREAS THE LEARNING MATHEMATICS - Laura Oktaviany Marantika (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Education is one of the most important things to prepare for future success in the era of globalization. Education has three main components, namely teachers, students, and curriculum. This third component cannot be eliminated in the teaching and learning process. Learning is an interaction that occurs between students and teachers as well as open source materials in the learning environment. The aim of this research is to apply the PBL model based on the GASING method to increase the mathematics learning focus of class IV students at SD Negeri 14 Banda Aceh. The research method used is descriptive qualitative, with data collection techniques through observation, interviews and documents. The results found after the research was carried out were that there was an increase in student focus which was seen with students being able to understand the abstract concept of whole numbers into concrete concepts, students could easily understand the differences in numbers (units, tens, hundreds, thousands, etc.) just by distinguishing colors. Ice cream sticks can help students develop their creativity during learning. Learning succeeded in increasing student focus as seen from student responses during learning. This research makes an important contribution in the field of education. this research emphasizes the importance of creating an effective and enjoyable learning process. Focusing on interactions between teachers, students, and relevant learning media allows students to increase their understanding of abstract mathematical concepts to become more concrete.